Efficacy of Biochar and NPK Fertilizer on Soil Properties and Yield of Okra (Abelmeschus esculentus L.) in Guinea Savanna Region of Nigeria (Journal of Environmental Bioremediation and Toxicology, 2022)
The efficacy of biochar and NPK fertilizer on soil properties and yield of okra (Abelmeschus  esculentus L.) is the central theme in this study. A randomized complete block design (RCBD) was used involving four (4) biochar rates (5, 10, 15 and 20 t/ha) and four (4) NPK (20:10:10) fertilizer rates (0, 100, 150 and 200 kg/ha) arranged factorially in 4 x 4 treatment combinations. Rice husk was used to make biochar since it was readily available and accessible in the study location. soil samples were collected at random locations on the field from two depths (0-15 cm and 15-30 cm) for analysis using standard procedure. Data were collected on plant height, number of leaves, number of branches, stem girth, days to 50% flowering, number of fruits per plant, fruit length, the weight of fruits and total yield. The result shows that biochar application at 20t/ha produced the highest plant height (67.75 cm), number of leaves(31.42), number of branches (16.00), stem girth (2.44 cm), number of fruit/plant (72.00), fruit length (14.33 cm), fruit weight (770.17 g) and total yield (855.74 kg/ha). Similarly, NPK at 200 kg/ha gave higher plant height (61.08 cm), number of leaves(26.75), number of fruit/plant (57.00), fruit weight (560.50 g) and total yield (622.78 kg/ha). The combination of 150 kg/ha and 200 kg/ha NPK fertilizer with 20 kg/ha biochar produced the highest yield (938.89 and 934.45 kg/ha) of okra which was at par. It can therefore be recommended that farmers in the study area can use biochar at 20 t/ha and NPK fertilizer at 150 kg/ha for optimum production of the okra plant.
Keywords: Biochar; Inorganic Fertilizer; Okra; Guinea Savanna; Soil Amendment